2010
DOI: 10.3164/jcbn.09-103
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal Mucosal Injury in Patients Taking Low-Dose Aspirin and the Role of Gastric Mucoprotective Drugs: Possible Effect of Rebamipide

Abstract: The present study was conducted to investigate the prevalence of mucosal injury in patients taking low-dose aspirin in Japan and examine the effect of gastric mucoprotective drugs on aspirin-related gastroduodenal toxicity. We selected 530 patients who had taken low-dose aspirin for 1 month or more after undergoing esophagogastroduodenoscopy from 2005 through 2006 at Teikyo University Hospital, Tokyo, Japan. Endoscopic records were retrospectively reviewed to determine the presence of massive bleeding and muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This indicates that the study by Yamamoto et al. was the single cause of statistical heterogeneity among the studies reporting on peptic ulcer.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…This indicates that the study by Yamamoto et al. was the single cause of statistical heterogeneity among the studies reporting on peptic ulcer.…”
Section: Resultsmentioning
confidence: 95%
“…Exclusion of any single study, except for the study by Yamamoto et al. , did not change the significance of the heterogeneity across the studies. When the study by Yamamoto et al.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Several gastric mucoprotective drugs other than PPIs have been found to prevent LDA-induced small intestinal mucosal injury to some degree; (1318) however, one study found no preventive effect of such drugs on LDA-induced small intestinal mucosal injury. (19) Of note, in the aforementioned reports, the dosages of gastric mucoprotective drugs were those recommended for the treatment of gastric/duodenal ulcers, the so-called “standard dosage”.…”
Section: Introductionmentioning
confidence: 99%